The Influence Of Forgiveness, Gratitude, And Duration Of Marriage Toward Marital Satisfaction On Wifes In South Jakarta - Firas Nabila Yusuf; Rena Latifa (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
The aim of this study is to examine how the relationships between forgivenss, gratitude, and duration of marriage toward marital satisfaction in wifes at South of Jakarta. Marital satisfaction is a personal feeling that strongly related to helath and happiness of marriage. Subjects for this study were 247 wifes at South of Jakarta and 50 wifes were apply for divorce at Religious Courts of South Jakarta. The instrument used was TRIM-18 Inventory (Transgression-Related Interpersonal Motivations-18 Inventory), GRAT (Gratitude, Resentment, and Appreciation Test), and EMS (Enrich Marital Satisfaction). Results indicated that forgiveness and gratitude have significant relationship with marital satisfaction. But, one of dimensions of forgiveness, benevolence motivations, doesn’t have significant relationship with marital satisfaction. So as duration of marriage. DOI:10.15408/tazkiya.v22i2.8408